NanoLINEN: Nanotoxicology Link Between India and European Nations - Dhawan, Alok (2012)
Nanotoxicology link between India and European Nations (NanoLINEN) is a consortium of 7 European laboratories and Indian Institute of Toxicology Research (CSIR Laboratory) from India to strengthen the research ties in the area of Nanomaterial Toxicology. The goal of this project is to develop robust risk assessment methodologies that will be useful for the community manufacturing and using nano-products.